2003
DOI: 10.1053/jlts.2003.50086
|View full text |Cite
|
Sign up to set email alerts
|

Liver organ allocation for hepatocellular carcinoma: Are we sure?

Abstract: Of patients with hepatocellular carcinoma (HCC), 70% to 90% present with cirrhosis. Accordingly, liver transplantation (LT), not liver resection, currently remains the only possibility of cure for these patients. Because there is a severe shortage of liver organ donors, not all patients in need can be offered LT. Therefore, transplant listing criteria simultaneously must determine the greatest number of suitable candidates for transplantation while rejecting the smallest number of those who could benefit from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
103
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 30 publications
5
103
0
2
Order By: Relevance
“…14 To support this idea, they reviewed pathological reports of all patients who underwent transplantation at the University of Pittsburgh with a diagnosis of hepatocellular carcinoma (HCC) and classified subjects according to three of the different staging systems that have been proposed to identify the best candidates for the procedure; namely, the Milano criteria, 6 the Pittsburgh criteria derived from a previous analysis, 15 and the recent criteria developed at the University of California San Francisco (UCSF). 13 Details and definitions of these staging systems are given in the report, but it is important to stress that although the Milano criteria are based on the findings of imaging techniques and used for clinical decision making, both the UCSF criteria and Pittsburgh assessments/proposals are derived from analysis of explanted livers when no treatment decision is to be taken.…”
mentioning
confidence: 99%
“…14 To support this idea, they reviewed pathological reports of all patients who underwent transplantation at the University of Pittsburgh with a diagnosis of hepatocellular carcinoma (HCC) and classified subjects according to three of the different staging systems that have been proposed to identify the best candidates for the procedure; namely, the Milano criteria, 6 the Pittsburgh criteria derived from a previous analysis, 15 and the recent criteria developed at the University of California San Francisco (UCSF). 13 Details and definitions of these staging systems are given in the report, but it is important to stress that although the Milano criteria are based on the findings of imaging techniques and used for clinical decision making, both the UCSF criteria and Pittsburgh assessments/proposals are derived from analysis of explanted livers when no treatment decision is to be taken.…”
mentioning
confidence: 99%
“…Resection of single tumors in patients with well-preserved liver function lead to remarkable outcomes (5-years survival exceeds 50%-60%) (34) . Early results after OLT in unselected patients with cirrhosis and HCC were poor, with early recurrence rates and 5-year survival of only 18%-49% (15,21,30,37,41,43,44,46) . Several small studies in the early 1990s suggested that recurrence-free survival could be improved by restricting transplantation to patients with two-three nodules or a single tumor < 3-5 cm in diameter (1,14,51) .…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al (64) from UCSF, reported a 5-year survival of 75% in patients with single tumor as large as 6.5 cm or a maximum of three tumors up to 4.5 cm and a cumulative tumor burden < 8 cm. With mostly retrospective data, some groups have independently tested these criteria (10,11,37) . These results have, however, been challenged because of the use of explants pathology, rather than preoperative imaging, as a determinant for the definition of the tumor stage.…”
Section: Discussionmentioning
confidence: 99%
“…Even the best preoperative imaging techniques can underestimate tumor burden in as many as 20% and significant progression in tumor size and number between imaging and LT after waiting period is not uncommon [9,10]. Additionally 10% to 15% nodules suspected to harbor HCC on pre-transplant imaging are reported benign following microscopic scrutiny of resection specimens by histopathologists [11].…”
mentioning
confidence: 99%